A Heterologous Viral Protein Scaffold for Chimeric Antigen Design: An Example pcv2 Virus Vaccine Candidate - Mascayano-Collado, C; Cortez-San Martin, M (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Recombinant vaccines have low-cost manufacturing, regulatory requirements, and reduced side effects compared to attenuated or inactivated vaccines. In the porcine industry, post-weaning multisystemic disease syndrome generates economic losses, characterized by progressive weight loss and weakness in piglets, and it is caused by porcine circovirus type 2 (PCV2). We designed a chimeric antigen (Qm1) to assemble the main exposed epitopes of the Cap-PCV2 protein on the capsid protein of the tobacco necrosis virus (TNV). This design was based on the Cap-N-terminal of an isolated PCV2 virus obtained in Chile. The virus was characterized, and the sequence was clustered within the PCV2 genotype b clade. This chimeric protein was expressed as inclusion bodies in both monomeric and multimeric forms, suggesting a high-molecular-weight aggregate formation. Pigs immunized with Qm1 elicited a strong and specific antibody response, which reduced the viral loads after the PCV2 challenge. In conclusion, the implemented design allowed for the generation of an effective vaccine candidate. Our proposal could be used to express the domains or fragments of antigenic proteins, whose structural complexity does not allow for low-cost production in Escherichia coli. Hence, other antigen domains could be integrated into the TNV backbone for suitable antigenicity and immunogenicity. This work represents new biotechnological strategies, with a reduction in the costs associated with vaccine development. © 2020 by the authors.